The Relationship between C-Reactive Protein Levels and The Prediction of Anastomotic Leakage : A Systematic Review - Erian Setiawan; Fitri Rachmadani (The International Journal of Medical Science and Health Research, 2026)
Introduction: Anastomotic leakage (AL) remains a devastating complication following gastrointestinal surgery, associated with increased morbidity, mortality, and prolonged hospital stay. C-reactive protein (CRP), an acute-phase inflammatory marker, has emerged as a potential early predictor of AL. This systematic review aims to evaluate the relationship between postoperative CRP levels and the prediction of anastomotic leakage across various surgical procedures. Methods: A systematic review was conducted following PRISMA guidelines. Comprehensive literature search identified studies evaluating CRP as a predictor of AL in adult patients undergoing gastrointestinal surgery with anastomosis. Studies were included if they reported quantitative data on CRP levels and AL rates. Data extraction encompassed surgical context, CRP measurement protocols, AL definition and incidence, and CRP predictive performance characteristics. Results: A total of 146 studies comprising 49,328 patients were included, covering colorectal (n=66), esophageal (n=33), gastric (n=18), and bariatric (n=8) surgeries, with others involving mixed or unspecified procedures. AL incidence ranged from 1.5% in bariatric surgery to 30.6% in esophagectomy. Median time to AL diagnosis was consistently 5-9 days postoperatively. CRP measurement protocols varied considerably, with postoperative days 3-5 demonstrating optimal predictive value. Pooled analysis revealed CRP cutoff values ranging from 120-200 mg/L on POD 3-5, with negative predictive values exceeding 90% in most studies. Significant heterogeneity existed in AL definitions, CRP measurement timing, and reported diagnostic accuracy. Discussion: Postoperative CRP demonstrates consistent utility as a negative predictive marker for AL, particularly between POD 3-5. Low CRP levels effectively rule out AL with high negative predictive value, potentially enabling safe early discharge. However, optimal cutoff values vary by surgical procedure and patient population. CRP performs best as a rule-out test rather than a rule-in test for AL. Conclusion: Serial CRP measurement represents a valuable, cost-effective tool for early prediction of anastomotic leakage. Standardized protocols and procedure-specific thresholds are needed to optimize clinical utility. Future research should focus on integrating CRP with other biomarkers and clinical risk scores to enhance predictive accuracy.